Elaboración, construcción y automatización de un sistema integral de control de temperatura para un criadero avícola a escala. - Vera Ramírez, Marlon Joel (2023)
Poultry farming in Ecuador is an activity that has been developed to a great extent in all sectors, Lanzaca is an area that has implemented this activity on a medium scale through the company "Avícola Lanzaca". One of the most important is temperature control in the houses where the birds are kept. Conventional systems are not effective, generating losses of birds due to heat shock. The automation of this activity allows to have a more efficient control of the temperature in the poultry house, reducing the mortality rate. The objective of this research is "To develop, build and automate an integral temperature control system for a poultry hatchery at scale", developing the work based on a scale model speeds up the testing process and the problems that may arise in the development of temperature control can be corrected quickly. To achieve this objective, the most relevant parameters and the existing and applicable temperature control systems were determined; a scale model was built based on a poultry house in the Lanzaca area, which was used as the object of the temperature control tests; the implementation of the temperature control was developed through mathematical modeling using specialized software (MATLAB®). The automation was based on PID control, where PI and PID controls excelled, allowing efficient temperature control during testing. The automation was developed on the Arduino platform and using the Visual Studio tool as the programming platform. Visual Studio as programming platform. Keywords: Automation, Poultry farming, Temperature control, PID control, Systems at scale